Analysis of microbiological hazards in turmeric tamarind traditional drink products - Lifiana, Aulia; Amarantini, Charis; Budiarso, Tri Yahya (Universitas Negeri Yogyakarta, 2024)
This study aimed to determine the presence of bacterial contaminants, specifically Escherichia coli, Salmonella sp., and Staphylococcus aureus, in turmeric tamarind traditional drink products according to the Indonesian National Standard (SNI 2019). The research was conducted using samples from 11 different locations in Yogyakarta. The samples were analyzed using Chromocult Coliform Agar (CCA), Salmonella Shigella Agar (SSA), and Baird Parker Agar (BPA) to isolate the specific bacteria. Further biochemical tests, including IMViC, Urease, and sugar fermentation tests, as well as confirmation using API 20E and API STAPH tests, were performed on the suspected isolates. The findings reveal that Escherichia coli, Salmonella sp., and Staphylococcus aureus were not detected in any of the samples. Thus, the traditional turmeric tamarind drink is considered safe for consumption according to the tested parameters. Keywords: turmeric tamarind, microbiological hazard, Klebsiella pneumoniae, Staphylococcus aureus. E. coli